The elements of dessert - Migoya, Francisco J. (New Jersey : Wiley, 2012)
"In this gorgeous and comprehensive new cookbook, Chef Migoya begins with the essential elements of contemporary desserts$1 (Blike mousses, doughs, and ganaches$1 (Bshowing pastry chefs and students how to master those building blocks before molding and incorporating them into creative finished desserts. He then explores in detail pre-desserts, plated desserts, dessert buffets, passed desserts, cakes, and petits fours. Throughout, gorgeous and instructive photography displays steps, techniques, and finished items. The more than 200 recipes and variations collected here cover virtually every technique, concept, and type of dessert, giving professionals and home cooks a complete education in modern desserts."s
The basic elements -- Pre-desserts -- Plated desserts -- Dessert buffets -- Passed-around desserts -- Cakes (entremets) -- Petits fours (mignardises).
Includes bibliographical references and index.
Keywords: DESSERTS